New species and distribution record of Schizostachyum (Poaceae, Bambusoideae) from Indonesia - Ritonga, Muhammad Azli; Syamsuardi; Nurainas; Maideliza, Tesri; Damayanto, I Putu Gede P.; Asmarayani, Rani; Nurjannah, Siti (Phytotaxa, 2025)
Schizostachyum sumpurkudusense Ritonga (Poaceae, Bambusoideae), a newly described bamboo species from Sumatra, Indonesia, is presented here along with an illustrations. This species bears similarities to Schizostachyum hantu S.Dransf. from Borneo (Sarawak, Malaysia) morphologically, particularly in having prominent culm and leaf sheath auricles with long bristles. However, it can be distinguished by several key features. Culm sheath ligules of S. sumpurkudusense are entire and glabrous, unlike the short, bristled ligules of S. hantu. Moreover, the culm sheath blades of S. sumpurkudusense are spreading, whereas they are erect when young and later become deflexed in S. hantu. The adaxial surface of the blades at the base of S. sumpurkudusense is either glabrous or occasionally bears scattered light brown to white hairs, contrasting sharply with the dense, long white hairs found in S. hantu. The manuscript includes a detailed description, photographs, illustrations, a distribution map, preliminary conservation status, and a comparative table with the most similar species. On the other hand, S. hantu was previously only known from Sarawak, Malaysian Borneo, and was absent from the Indonesian part of Borneo (Kalimantan). Recent exploration in East Kalimantan, Indonesia, and based on specimen examination at the Herbarium Wanariset (WAN), confirmed the presence of S. hantu in Kalimantan. Thus, this marks the first official record of S. hantu in Indonesia, increasing the number of known Schizostachyum species in the country.